2021
DOI: 10.3390/vaccines9121385
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anxiety on Readiness for COVID-19 Vaccination among Polish Nursing Undergraduate Students: Nationwide Cross-Sectional Study

Abstract: The COVID-19 pandemic had a huge impact on the mental health of people around the world, and it increased the level of fear of infection and anxiety about the consequences of the disease caused by the SARS-CoV-2 virus. We examined the relationship between the level of anxiety among nursing students and their knowledge about COVID-19 vaccination. In addition, we explored the correlations among the level of anxiety, knowledge about vaccination, and the willingness to vaccinate against COVID-19. A total of 790 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
2
4
0
1
Order By: Relevance
“…This result is in line with Cao, et al, (2020) who studied the psychological impact of the COVID-19 epidemic on college students in China, and reported that, the anxiety about the COVID-19 vaccine was high among college students in China. This might have been connected to the virus' impact on their academic pursuits and future employment, while it is in congruent with another study by Gotlib, Jaworski, Wawrzuta, Sobierajski, and Panczyk (2021), who found in their research, that the level of anxiety among the students surveyed was low; more than one third of study participants reported no anxiety at all. COVID-19-related anxiety and health-related fears were associated with higher vaccine acceptance, whereas the fear of social and economic consequences showed the contrary direction.…”
Section: Discussionsupporting
confidence: 81%
“…This result is in line with Cao, et al, (2020) who studied the psychological impact of the COVID-19 epidemic on college students in China, and reported that, the anxiety about the COVID-19 vaccine was high among college students in China. This might have been connected to the virus' impact on their academic pursuits and future employment, while it is in congruent with another study by Gotlib, Jaworski, Wawrzuta, Sobierajski, and Panczyk (2021), who found in their research, that the level of anxiety among the students surveyed was low; more than one third of study participants reported no anxiety at all. COVID-19-related anxiety and health-related fears were associated with higher vaccine acceptance, whereas the fear of social and economic consequences showed the contrary direction.…”
Section: Discussionsupporting
confidence: 81%
“…This anxiety can interfere with the program before, during, and after vaccination. Anxiety results in low participation and physical complaints due to anxiety (Gotlib et al, 2021). The study results align with Meriem et al; health education reduces the anxiety of the elderly facing the transmission of COVID-19 (Syamson & Nurdin, 2021).…”
Section: Intragroup and Intergroup Comparison In Term Of Effect Knowl...supporting
confidence: 88%
“…An interesting study was conducted by Gotlib et al in a group of 790 nursing students in Poland, in which the researchers sought a correlation between the level of anxiety among the students and their knowledge of COVID-19 vaccines and between the level of anxiety, the knowledge of the vaccinations and the will to vaccinate against COVID-19. It turned out that the anxiety level among the nursing students was low, with no direct correlation between the knowledge of the vaccines and the anxiety level [64].…”
Section: Discussionmentioning
confidence: 92%